Exploring gender-wise, sector-wise, and grade-wise difference among secondary school students’ reading habits - Aqeela Samuel; Nisar Abid; Asmaa Azeem; Rukhsana Bashir (Institute of Advanced Engineering and Science, 2023)
This study was conducted to examine students’ perceptions regarding reading habits and to explore gender-wise, sector-wise, and grade-wise differences in secondary school students’ reading habits. The students (N=538) who participated in this cross-sectional survey were selected through a non-proportional stratified random sampling technique from district Lahore. The researchers developed a questionnaire comprised of four subscales (perceptions, purpose, preferences, and problems in reading) to measure students reading habits. They ensured the validity of the instrument from experts and calculated the reliability that was Cronbach’s alpha=0.802. Data were analyzed by using different statistical techniques (mean, standard deviation, and independent samples t-tests). The results of descriptive statistics indicated that students gave more preferences to reading than perceptions about reading, the purpose of reading, and problems in reading. However, the least contributing factor was problems in reading. Whereas the findings of independent samples t-tests showed a significant difference in students’ perceptions about reading habits based on gender and class. However, an insignificant difference was found in students’ perception of reading habits based on sector-wise (public and private) schools. Books of students’ interests may be provided in libraries to encourage them to read. Moreover, teachers may also arrange more reading activities to enhance students’ reading skills.